Aesthetic Analysis of the Audiovisual Work of Alberto García-Alix at the Beginning of the 21st Century - Guerrero Muñoz, Aramis (Escritura e Imagen, 2024)
The present study aims to demonstrate the existing correlation between the aesthetics of the audiovisual work of renowned photographer Alberto García-Alix, developed during the first decade of the current century, and the Aesthetic theories proposed by Eugenio Trías in his book Lo bello y lo siniestro (1982) and by Jose Luis Pardo in his book Estética de lo peor (2015). Throughout this research, the most significant characteristics of the audiovisual pieces that the author created during his stay in Paris between the years 2003 and 2006, collected in the trilogy "Tres vídeos tristes," which includes "Mi alma de cazador en juego" (2003), "Extranjero de mí mismo" (2004), and "Tres moscas negras" (2006), will be thoroughly examined. Alongside the analysis of this trilogy, the «audiovisual» work that is recognized as his greatest artistic maturity to date, "De donde no se vuelve" (2008), will also be analysed.
Keywords: photography; Spanish art; Alberto García-Alix; Eugenio Trías; José Luis Pardo